2019
DOI: 10.1007/s12119-019-09628-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Comparison of Sensory Preferences in Romantic Attraction

Abstract: Various physical characteristics of a partner-visual, auditory, tactile and kinetic, olfactory, and gustatory-can affect human mate choice and romantic attraction. Evolutionary factors, as well as socioeconomic and cultural parameters play their role in these sensory preferences. A series of studies in societies varying in social, economic, and cultural parameters (10 samples in six countries with 2740 participants in total) explored cross-cultural similarities and differences of sensory preferences that peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Research linking these two dimensions of Hofstede’s model and relationships has also been sparse. While some studies have shown that individuals from countries with varying time orientation and indulgence levels differ in their partner choices and relational goals (Karandashev et al, 2020; Lu et al, 2021), there is no conclusive evidence if and how their dating motivations and practices differ. Because of this lack of research, we propose a research question to explore possible associations between the two cultural dimensions from Hofstede’s model and corresponding advertising appeals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research linking these two dimensions of Hofstede’s model and relationships has also been sparse. While some studies have shown that individuals from countries with varying time orientation and indulgence levels differ in their partner choices and relational goals (Karandashev et al, 2020; Lu et al, 2021), there is no conclusive evidence if and how their dating motivations and practices differ. Because of this lack of research, we propose a research question to explore possible associations between the two cultural dimensions from Hofstede’s model and corresponding advertising appeals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research about romantic love has predominantly concentrated in its multidimensional complexity (Clark & Mills, 1979;Hatfield & Walster, 1978;Hazan & Shaver, 1987;Karandashev et al 2020;Sternberg, 1986). The research presented in this work employed the comprehensive love theory developed by Lee (1973Lee ( , 1977Lee ( , 1988.…”
Section: The Lee's Colors Of Love Modelmentioning
confidence: 99%
“…Typically, it refers to positive reactions that can be divided into four components: cognitive (positive thoughts and beliefs), affective (positive feelings and emotions), motivational (a desire to approach the other), and behavioral (standing or sitting closer) ( Wurst and Back, 2018 ). Cross-cultural studies on attraction have demonstrated that the bases of relationships are not random and are strongly linked to basic mechanisms of attraction ( Eastwick, 2013 ; Zarubko et al, 2016 ; Karandashev et al, 2020 ). Mechanisms of attraction are important because of the impact that attraction processes have on individual’s life, and because increasing knowledge about these mechanisms improves our understanding of ongoing relationship dynamics ( Simpson, 1990 ; Finkel et al, 2007 ; Schindler et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%